ANALISIS FAKTOR YANG MEMPENGARUHI MINAT BACA SISWA KELAS 2 SDN 02 GAYAMSARI SEMARANG - Bagus Oktavian Rahman; Kartinah; Ngurah Ayu Nyoman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Interest in reading is someone interested in reading and has a strong desire to read, evaluate, and understand the material. Thus, various factors support the low enthusiasm of students in reading. The purpose of this study was to find out how the reading interest of grade 2 students at SDN 02 Gayamsari Semarang. This study aims to determine students' reading interest in grade 2 SDN 02 Gayamsari. The research method used is the descriptive qualitative method. The findings show that some students' interest in reading is lacking, but most students' interest in reading is positive. There are 2 internal and external factors identified as factors of students' interest in reading based on the findings of data analysis. Internal elements come from students, such as a lack of motivation to read, students' lack of feelings, attention to books and the benefits of reading, and reading books at the request of the teacher. there is an impact of smartphone use. The steps taken are by giving motivation, continuous attention to grade 2 students, and attention to increasing interest in reading. Factors that influence interest in reading outside are the role of the teacher, environment, family, and facilities. Teachers must use theory or learning strategy components as learning principles so that learning is well received by students and becomes easier.